2020
DOI: 10.3389/fmed.2020.00530
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Demographics and Clinical Characteristics Related to the Expression of Angiotensin-Converting Enzyme 2, a Receptor of SARS-CoV-2

Abstract: Objective: Coronavirus disease 2019 (COVID-19) was first reported in Wuhan, China, and has rapidly spread throughout the world. It has been reported that angiotensin-converting enzyme 2 (ACE2) is one of the major cellular entry receptors of SARS-CoV-2; thus, high ACE2 expression may increase susceptibility to infection. Therefore, we analyzed the expression of ACE2 in the blood to identify the individuals who may be susceptible to infection. Methods: In total, 229 subjects were enrolled in this study, and reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Most studies indicated that COVID-19 patients with COPD or smokers have an increased expression of ACE2 in bronchial epithelial cells in the respiratory tract as compared with healthy subjects [17][18][19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies indicated that COVID-19 patients with COPD or smokers have an increased expression of ACE2 in bronchial epithelial cells in the respiratory tract as compared with healthy subjects [17][18][19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Placental tissue was sampled as described above and used to measure the expression of SARS-CoV-2 receptors: ACE2 (Abcam; Discovery Drive, Cambridge, United Kingdom) and TMPRSS2 (Aviva Systems Biology, San Diego, CA) were assayed using commercial highly specific enzyme-linked immunosorbent assay kits validated for human tissue extracts. 19,20 Their inter-assay and intra-assay coefficients of variation were <12% and <10%, respectively. ACE2 and TMPRSS2 concentrations were corrected for the total protein content in each sample, measured by a colorimetric kit detecting copper reduction by proteins using bicinchoninic acid (Thermo Fisher, Waltham, MA).…”
Section: Cases Of Transplacental Transmissionmentioning
confidence: 96%
“…Li S, et al ( 27 ) reported that increased levels of sACE2 and ACE2 gene expression were found in female and elderly patients, but another study by Muus C, et al ( 28 ) found increased levels of ACE2 gene expression in male and elderly patients. However, our study showed no difference between the patients’ gender and both levels of sACE2 and ACE2 gene expression ( p = 0.074 and p = 0.741, respectively), but a significant decrease was found in both serum ACE2 and ACE2 gene expression levels as patients aged (both p <0.001) ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%